Letter (copy) : General Workers' Union of Spain - Bell, Ernest A.
001-0156-001 International. EAB/DT/966. 1st July, 1942. Mr. W. Carrillo, Trade Union Group of Spanish workers in Great Britain, Transport House, Smith Square, S.W.I. Dear Comrade Carrillo, GENERAL WORKERS' UNION OF SPAIN I have tried unsuccessfully to make personal contact with you to-day to inform you of the invitation which we have received from the U.G.T. (General Workers' Union or Spain) to appoint a fraternal delegate to attend their first general conference which is to take place in the Hogar Espanol, 22, Inverness Terrace, W.2. on Saturday and Sunday, July 4th and 5th. For your information I am enclosing a copy of this invitation, to which we do not propose to reply. Yours sincerely, International Department. Invitation. 292/946/1/156